Women Empowerment through Self Help Group in Haryana: Examining the Impact of Self Help Groups on Women Empowerment in Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The campaign was first announced by Prime Minister Narendra Modi in his 15 August 2015 address from the Red Fort. It is focused on to restrict role of States in policy domain and to get rid of license raj and hindrances like in land permissions, foreign investment proposal, environmental clearances. It was organized by Department of Industrial Policy and Promotion (DIPP). The present study analyzed the women empowerment through startup India. By Self Help Group (SHG) women empowerment of various aspects like as educational empowerment, social empowerment, economically empowerment and political empowerment and Standup India initiative empowerment among SCsSTs, women communities.